Perancangan Sistem Inventory Berbasis Web Dengan Barcode Scanner Untuk Pengelolaan Barang Pada Cv D`Lantik Art Project Menggunakan Metode Agile - Rangga Prasetya, Aditya; Haikal Putra, Dzaki; Kencana, Wisnu; Haryono, Wasis (AMIK STIEKOM SUMATERA UTARA, 2025)
− CV D'Lantik Art Project is a company engaged in the art industry, especially in providing decorations for events in malls, hotels, and other public places. In its operational process, the recording of goods is still done manually using Microsoft Excel, which often causes delays in reporting and potential recording errors. Along with the development of technology, the implementation of a web-based inventory system is an important solution to improve efficiency and accuracy in managing stock items. This internship aims to design and develop a web-based inventory system with barcode scanning features using the Agile development method. This method was chosen because of its flexibility and iterative approach in planning, implementing, testing, and maintaining the system. The result of this activity is an inventory website that can help companies in recording incoming and outgoing goods more efficiently and in real-time. It is hoped that this system will be able to reduce human error and increase the effectiveness of stock monitoring to support the company's project needs.